2020
DOI: 10.1177/0192513x20906540
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Influence? Gender, Partner Pregnancy Desires, Fertility Intentions, and Birth Outcomes in U.S. Heterosexual Couples

Abstract: Competing hypotheses exist with regard to how men’s and women’s pregnancy desires and intentions are associated with births among contemporary heterosexual couples. There are compelling cultural and structural reasons to support either the hypothesis that men’s desires and intentions (patriarchal) or that women’s desires and intentions (matriarchal) will have more influence, or that both partner’s desires and intentions will be associated with births (mutual influence). In addition, patterns of change are like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
(80 reference statements)
0
8
0
Order By: Relevance
“…Achievement of tasks in each stage strongly correlates with adjustment and fulfillment of marriage expectations (Peixoto-Freitas et al, 2020). Fertility is affected by gender roles, especially in the transition from marriage to childbearing, and women typically bear the responsibility for fertility problems (Ray et al, 2020). The results of this study show that women who seek fertility treatment thought that childbirth was a very natural thing and represented an expected change in the life course.…”
Section: Discussionmentioning
confidence: 99%
“…Achievement of tasks in each stage strongly correlates with adjustment and fulfillment of marriage expectations (Peixoto-Freitas et al, 2020). Fertility is affected by gender roles, especially in the transition from marriage to childbearing, and women typically bear the responsibility for fertility problems (Ray et al, 2020). The results of this study show that women who seek fertility treatment thought that childbirth was a very natural thing and represented an expected change in the life course.…”
Section: Discussionmentioning
confidence: 99%
“…This study referred to studies in the extant literature [ 56 , 57 , 58 , 59 , 60 ] to determine the control variables to be used, 12 in total. These were gender, age, education, nationality, belief, marital status, political parties, health, pension, fixed assets, family income and number of children.…”
Section: Data Variables and Methodsmentioning
confidence: 99%
“…A German-based study showed symmetrical effects of both partners’ desires for children (Bauer & Kneip, 2013 ). In contrast, a study employing couple data from the US reported that women’s desires were associated both with first and subsequent births, while men’s desires were only indirectly associated with the latter (Ray et al, 2020 ). In a study about couples’ childbearing behavior in Italy (Testa et al, 2011 ), women were found to have a stronger effect on fertility decisions than their male partners.…”
Section: A Couple Perspective: a Dyadic Extension Of The Tpbmentioning
confidence: 97%